2003
DOI: 10.1182/blood-2003-03-0861
|View full text |Cite
|
Sign up to set email alerts
|

Clonal dominance of chronic myelogenous leukemia is associated with diminished sensitivity to the antiproliferative effects of neutrophil elastase

Abstract: Clinical observations suggest that in chronic myelogenous leukemia (CML), the Philadelphia chromosome (Ph+) clone has a growth advantage over normal hematopoiesis. Patients with CML have high levels of neutrophil elastase, which has recently been shown to antagonize the action of granulocyte-colony-stimulating factor (G-CSF) and other growth factors. We therefore compared the effect of elastase on the growth of normal and CML progenitor cells. In 10-day suspension cultures of normal or CML CD34+ cells suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Elastase produced by chronic myelogenous leukemia (CML) neutrophils preferentially suppresses normal hematopoiesis. 20 Elastase can cleave G-CSF and its receptor, abolishing its proliferative effect on normal human CD34 ϩ progenitor cells. 21,22 Moreover, proteolytic processing by elastase was recently suggested to play an important role in the development of leukemogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Elastase produced by chronic myelogenous leukemia (CML) neutrophils preferentially suppresses normal hematopoiesis. 20 Elastase can cleave G-CSF and its receptor, abolishing its proliferative effect on normal human CD34 ϩ progenitor cells. 21,22 Moreover, proteolytic processing by elastase was recently suggested to play an important role in the development of leukemogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…1 The efforts to decrease the risk of graft-versus-host disease (GVHD) as a major cause of transplant-related mortality by depleting T cells from the graft resulted in an increased incidence of CML relapse. 2 These observations revealed that donor T cells representing the mediators of GVHD are also capable of inducing therapeutic HNE plasma levels pre-IM treatment. n Po0.05, nnn Po0.005 with respect to normal plasma or marrow control.…”
mentioning
confidence: 93%
“…2 Elafin is a naturally occurring inhibitor of HNE, and can restore normal proliferation when added to mixed CML/normal cell cultures (El-Ouriaghli et al Blood 2003; 102: 230a; abstract). We sought to determine whether HNE levels are elevated in CML bone marrow (BM) and peripheral blood (PB) samples taken pre-and post-treatment with the tyrosine kinase inhibitor, imatinib mesylate (IM) and to determine any correlation with disease stage.…”
mentioning
confidence: 99%
“…1 These 2 proteins are aberrantly expressed in human myeloid leukemias such as chronic myeloid leukemia (CML). 2 Overexpression of PR3 may be important in maintaining a leukemia phenotype because inhibition of PR3 synthesis by PR3-antisense oligonucleotides halts cell division and drives differentiation of the HL-60 promyelocytic leukemia cell line. 3 HNE is also overexpressed in leukemia patients and has been shown to suppress tumorigenic hematopoietic progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…3 HNE is also overexpressed in leukemia patients and has been shown to suppress tumorigenic hematopoietic progenitors. 2 Thus, both proteins are attractive as vaccine targets.…”
Section: Introductionmentioning
confidence: 99%